Remember Kirkland Lake: The Gold Miners' Strike of 1941-42 - MacDowell, Laurel Sefton (Canadian Scholars' Press, 2001)
[This book] tells the story of one of the most important industrial disputes in Canadian labour history. This strike united the Canadian labour movement around the demand for collective bargaining legislation, which it won in 1944 and which remains central to our industrial relations system. The book provides a comprehensive analysis of all the factors in this dramatic dispute. At the community level, a social history approach examines the local living and working conditions of the miners and their families, the role of the women in the dispute, and the ethnic makeup of the workforce. -- Publisher's description
Keywords: Canada; Gold Miners' Strike, Kirkland Lake, Ont., 1941-1942. Collective bargaining; History; Mining industry